Behaviour of explosively welded impedance-graded multi-metal composite plates under near-field blast loads. (November 2019) - Fernando, P.L.N.; Mohotti, Damith; Remennikov, Alex
Highlights: A composite plate was designed by reducing the impedance through its thickness. Explosive welding is a feasible technique to develop the composite plate. Composite plates did not show scabbing failure for very close-in detonations. Impedance-grade composite plates resist blast loads through its higher ductility. Significant weight reduction can be achieved through the composite plates. Abstract: This paper presents a comprehensive analysis of the blast response of functionally graded composite metallic plates, fabricated using explosive welding. Explosive welding is a solid-state welding technique, which has previously shown capabilities in bonding metals that have different chemical and mechanical properties. Impedance, which is the product of volumetric mass density and wave propagation velocity for a given material, was chosen as the function when designing the graded composite plates. The performance of two composite plate configurations, namely, Steel-Titanium-Aluminium and Steel-Brass-Aluminium were compared with a monolithic steel configuration of equal overall plate dimensions. The plates were subjected to highly intensive blast loads produced by detonation of the 250 g cylindrical Composition-B charges at standoff distances between 20–65 mm and spherical 1 kg Nitromethane charges at standoff distances of 200 mm and 250 mm. Detailed numerical models of near-field loading of the monolithic and composite plates were developed using the non-linear finite element analysis software LS-DYNA and validated using the experimental deformation measurements. Experimental evaluation of the impedance-graded explosively- welded composite plates has been carried out for the first time and herein lies the novelty of the work presented in the paper. It was observed that the impedance graded composite plates, which were lighter in density than the monolithic plates, resisted the highly intensive blast loads through their enhanced ductility. Graphical abstract: Image, graphical abstract